IoT based Clinical Sensor Data Management and Transfer using Blockchain Technology - Wang, Haoxiang (Journal of ISMAC, 2020)
There has been revolutionary developments in the healthcare industry with the advancement of technology over the past years. Internet of Things, Cloud Computing, Blockchain technology, lab-on-chip, non-invasive and minimally invasive surgeries and so on has simplified several dreadful diseases. The research as well as healthcare industry have been greatly impacted by these new technologies. Clinical exams and self-health tracking can be done by means of miniaturized healthcare sensors that are powered by IoT. They help in early diagnosis and treatment guidance by clinicians at remote locations without directly being in contact with the users. The access control structures and inconsistent security policies have been a hinderance in meeting the security requirements of these data. Blockchain based smart contracts and enterprise-distributed ledger framework can be used for monitoring the vital signs of the patient. This enables accessing medical information of patients globally at any time along with immutable and extensive history log. In comparison with the traditional patient monitoring system, the proposed system offers better monitoring, improved connectivity and enhanced data security.